IMPROVING COMPUTER ENGINEERING AND INFORMATION TECHNOLOGIES UNDERGRADUATE STUDENTS’ TRAINING THROUGH COMBINATION OF FORMAL, NON-FORMAL AND INFORMAL LEARNING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The paper analyses benefits of combining formal, non-formal and informal learning in Computer Engineering and Information Technologies undergraduate students’ training. The results of research conducted in the 2017/2018 academic year are shown. A total of 106 students earning BA in Computer Engineering and Information Technologies at National University of Life and Environmental Sciences of Ukraine volunteered to participate in the research. The aim of the research was to investigate the influence of combining formal, non-formal and informal learning on improving Computer Engineering and Information Technologies undergraduate students’ training through the increase in their general self-efficacy. To collect data from 106 computer engineering and information technologies undergraduate students we applied a mixed methods approach implying the combination of qualitative and quantitative methods. The quantitative data were collected using a pre-test and a post-test based on a questionnaire on general self-efficacy. Qualitative methods included classroom observations and interviews with computer engineering and information technologies undergraduate students. The authors compared the results obtained in the experimental and control groups and drew conclusions concerning the positive effects of combining formal, non-formal and informal learning on improving Computer Engineering and Information Technologies undergraduate students’ training through the increase in their general self-efficacy.